PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, UNTUK MENINGKATKAN INDEKS PEMBANGUNAN MANUSIA - Mahendra Putra, Putu Gde; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi, 2015)
Human Development is an index that measures the performance of human development indicators measuring them based 3 Life Expectancy, Education and Life Worth. Each region has a source of income derived from revenue (PAD), the General Allocation Fund (DAU) and Special Allocation Fund (DAK), suspected source of revenue that is said to give effect to the Human Development Index (HDI). This study is the conclusion of some of the same research and research objectives were to determine how much revenue, DAU and DAK can increase the HDI. The results show PAD, DAU, DAK significant positive effect on the HDI.
Keywords: PAD, DAU,DAK and HDI